The Archaeology of Cyprus from 1200-300 B.C. with Special Reference to Foreign Connections. Vol. II (Illustrations). M.A. - Birmingham, Jean Margaret (2000)
Typescript; 1. Introduction; 2. Evidence from written sources (12-14 Hittite records; 24-26 Assyrian inscriptions); 3. Sites; 4. Architecture; 5. Pottery; 6. Metals; 7. Sculpture; 8. General conclusions.